2018
DOI: 10.1073/pnas.1815410115
|View full text |Cite
|
Sign up to set email alerts
|

PYL8 mediates ABA perception in the root through non-cell-autonomous and ligand-stabilization–based mechanisms

Abstract: The phytohormone abscisic acid (ABA) plays a key role regulating root growth, root system architecture, and root adaptive responses, such as hydrotropism. The molecular and cellular mechanisms that regulate the action of core ABA signaling components in roots are not fully understood. ABA is perceived through receptors from the PYR/PYL/RCAR family and PP2C coreceptors. PYL8/RCAR3 plays a nonredundant role in regulating primary and lateral root growth. Here we demonstrate that ABA specifically stabilizes PYL8 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 39 publications
0
52
0
1
Order By: Relevance
“…In contrast, PYR1 did not co‐immunoprecipitate with RGLG1‐GFP and PP2CA (Figure a). Therefore, it seems that ABA facilitates the formation of the PYL8–RGLG1–PP2CA complex by the upregulated transcription of PP2CA , which leads to increased PP2CA levels, the stabilization of PYL8 protein levels and high‐affinity binding of PP2CA to PYL8 (Santiago et al ., ; Antoni et al ., ; Irigoyen et al ., ; Wu et al ., ; Belda‐Palazon et al ., ). Indeed, using transient expression in tobacco cells, we demonstrated that increased PP2CA levels lead to an enhanced recruitment of RGLG1 in the nucleus (Figure b–d).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In contrast, PYR1 did not co‐immunoprecipitate with RGLG1‐GFP and PP2CA (Figure a). Therefore, it seems that ABA facilitates the formation of the PYL8–RGLG1–PP2CA complex by the upregulated transcription of PP2CA , which leads to increased PP2CA levels, the stabilization of PYL8 protein levels and high‐affinity binding of PP2CA to PYL8 (Santiago et al ., ; Antoni et al ., ; Irigoyen et al ., ; Wu et al ., ; Belda‐Palazon et al ., ). Indeed, using transient expression in tobacco cells, we demonstrated that increased PP2CA levels lead to an enhanced recruitment of RGLG1 in the nucleus (Figure b–d).…”
Section: Resultsmentioning
confidence: 97%
“…Given that PYL8–ABA–PP2CA complexes have been previously identified (Antoni et al ., ), the most likely explanation is that ternary complexes are formed in the presence of ABA. A lower input of PYL8 and PP2CA is observed in the absence of ABA treatment because of the enhanced ubiquitination of PYL8 (Belda‐Palazon et al ., ) and reduced PP2CA transcript levels (Wu et al ., ). In contrast, PYR1 did not co‐immunoprecipitate with RGLG1‐GFP and PP2CA (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most phenotypic defects of BR biosynthetic mutants can be rescued by exogenous BR treatment. As with other hormones, plant responses to exogenous BR application are dosedependent, with growth-promoting effects observed for lower concentrations and growth retardation when higher doses are used (Chaiwanon and Wang, 2015;Belda-Palazon et al, 2018). Initial dissection of BR signaling at the tissue level has provided clues that the epidermal layer is the site of the most intensive BR signaling events, as the dwarf phenotypes of BR receptor or BR biosynthetic enzyme mutants could be rescued by epidermisspecific expression of the mutated genes (Savaldi-Goldstein et al, 2007).…”
Section: Br Signaling Is Tissue-specificmentioning
confidence: 99%